Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s00405-016-3919-3
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemotherapy-based larynx preservation program for locally advanced hypopharyngeal cancer: oncologic and functional outcomes and prognostic factors

Abstract: To evaluate oncologic and functional outcomes and prognostic factors in patients with locally advanced hypopharyngeal cancer included in an induction chemotherapy (ICT)-based larynx preservation program in daily clinical practice. All patients with locally advanced (T3/4, N0-3, M0) hypopharyngeal squamous cell carcinoma, technically suitable for total pharyngo-laryngectomy, treated by docetaxel (75 mg/m(2), day 1), cisplatin (75 mg/m(2), day 1) and 5-fluorouracil (750 mg/m(2)/day, day 1-5) (TPF)-ICT (2-3 cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 13 publications
1
25
0
Order By: Relevance
“…However, a concern is raised whether this approach leaves the patient with a functioning larynx . Bozec noted that those patients who responded to induction chemotherapy were more likely to require permanent enteral nutrition . Lim recorded a 3‐year progression‐free survival of 42% with concurrent CRT, worse than, with comparable treatment, at other head and neck sites .…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…However, a concern is raised whether this approach leaves the patient with a functioning larynx . Bozec noted that those patients who responded to induction chemotherapy were more likely to require permanent enteral nutrition . Lim recorded a 3‐year progression‐free survival of 42% with concurrent CRT, worse than, with comparable treatment, at other head and neck sites .…”
Section: Discussionsupporting
confidence: 56%
“…However, it was “performance status” only that was predictive of improved overall survival . Bozec recorded a similar circumstance of better larynx preservation with induction chemotherapy of docetaxel, cisplatin, and 5‐fluorouracil . However, a concern is raised whether this approach leaves the patient with a functioning larynx .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Feeding tube dependence has a major impact on quality of life in head and neck patients, much more than tracheostomy dependence, according to the work of Terrell et al Reported rates of feeding tube dependence after head and neck radiotherapy vary between 3% and 53% . Wopken et al reported a 13% dependence at 6 months.…”
Section: Discussionmentioning
confidence: 99%